Integrated internal and external exposure models for dimethylformamide risk assessment and health risk monetization - Na Cai; Yuan Zhao; Fanwei Xu; Minyun Jiang; Lei Han; Baoli Zhu; Boshen Wang (Ecotoxicology and Environmental Safety)
Long-term exposure to chemicals can cause chronic health damage in occupational workers, and traditional risk assessment methods are no longer sufficient to comprehensively evaluate these chronic effects. Therefore, it is crucial to explore risk assessment methods that are more suited to the typical exposure environments of occupational workers. Herein, we conducted on-site concentration measurements and health effect analyses of 1040 dimethylformamide-exposed workers at 19 enterprises in Jiangsu Province, performed probabilistic health risk assessment of the sampling results, and report the first definition of the liver injury weights. Based on a simplified pharmacokinetic model, external exposure was reconstructed using the biomarker concentration of N-methylcarbamoyl hemoglobin (NMHb) for dimethylformamide (DMF). The reconstructed concentrations were then used to perform a risk assessment through the U.S. Environmental Protection Agency (EPA) model, and the results were compared with those obtained prior to the reconstruction. Monetized health risk results indicated that the film stripping and inspection positions workers faced substantial risk requiring special attention, and the health risk was higher for men than women. The internal exposure model had higher sensitivity and applicability than the external exposure model. Among all job categories,film stripping had the highest risk values, disability-adjusted life years,and willingness to pay (average of $3038.07/year). This study provides theoretical support for social and occupational protection authorities determining reasonable compensation for chronic damage health damage among occupational personnel.